Entry Deterrence in Postal Service Markets - Patrick Frank Ernst Beschorner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
In this paper we analyze the incentive of the German postal service (Deutsche Post AG, DPAG) to increase quality in the light of the upcoming liberalization of the postal services market. Currently, there would be no incentive for DPAG to increase its quality if the market were not to be liberalized in six months. Therefore, we suggest that the current changes in market regulation have motivated this quality improvement. In particular we show that this rise in quality is only profitable to DPAG because it renders entry less profitable or even impossible. However, consumers benefit from higher quality, whether entry is deterred or accommodated.
Keywords: L51; L41; L12; 330; regulation; liberalization; postal services; Postbeförderung; Deregulierung; Dienstleistungsqualität; Markteintritt; Deutschland